Optimalisasi Pemanfaatan Sekam Padi Menjadi Briket Ramah Lingkungan Di Desa Pematang Kasih - Anisa Puspita; Cindy Rayani Ibrahim Sinulingga; Dira Finanta; Khairunnisa (Pusat Riset dan Inovasi Nasional, 2025)
This research aims to optimize the use of rice husks to produce environmentally friendly briquettes in Pematang Kasih Village, Pantai Cermin District, Serdang Bedagai Regency, North Sumatra Province. This activity was implemented through the 2025 Community Service Program (KKN) of the State Islamic University of North Sumatra, using qualitative methods and a field study approach. Observations were conducted to determine the community's continued disposal of rice husk waste without meaningful use. Based on the observations, KKN students then conducted outreach and hands-on practice of making rice husk briquettes with the village community. The results showed that the community enthusiastically participated in the outreach and began to understand the economic values ​​and environmental benefits of rice husk processing. The resulting briquettes can be used as an alternative fuel for household needs. This program successfully raised public awareness of the importance of agricultural waste management and opened new economic opportunities based on environmentally friendly energy.